Functional structure and approximation in econometrics - Barnett, William A.; Binner, Jane M., 1961- (Amsterdam ; Oxford : Elsevier, 2004)
A competition.SummaryThis book contains state-of-the-art cumulative research and results on functional structure, approximation and estimation for: individual economic agents; aggregation over those agents; and equilibrium solution stochastic processes. Contributions to time series modeling and inference in the time domain and the frequency domain are also covered.
Includes bibliographical references and index.
oif 22/07/14
Loan
Keywords: Econometrics; Functional analysis; Approximation theory